2011
DOI: 10.2533/chimia.2011.835
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Interference of Biological Systems with Natural Products

Abstract: Chemical compounds isolated from natural sources offer unique opportunities to understand life on a molecular level. In this account, an overview over different natural products investigated in our research group over the last decade is presented. We have shown that protein localization in living cells can be controlled by anguinomycins and derivatives. Furthermore, a truncated analog, SB640, was discovered that retained much of the natural product potency. Detailed studies of the iron chelator anachelin led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This implies that the modification of Ang-D into SB640 caused a significant reduction in molecular weight, size and volume, which could in turn enhance intestinal absorption and cellular uptake with respect to pharmacokinetic activity. This was in line with previous experimental studies which reported ~60% reduction in size [ 24 , 47 ]. The influence of a relatively high MW on Ang-D relative to bioactivity is further reflected by the number of rotatable bonds which is a good descriptor of molecular flexibility [ 97 ].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This implies that the modification of Ang-D into SB640 caused a significant reduction in molecular weight, size and volume, which could in turn enhance intestinal absorption and cellular uptake with respect to pharmacokinetic activity. This was in line with previous experimental studies which reported ~60% reduction in size [ 24 , 47 ]. The influence of a relatively high MW on Ang-D relative to bioactivity is further reflected by the number of rotatable bonds which is a good descriptor of molecular flexibility [ 97 ].…”
Section: Resultssupporting
confidence: 93%
“…This technique enables the synthesis of tailored bioactive fragments with reduced molecular weight and structural complexity when compared to the parent bioderived compound [ 14 ]. Moreover, while the number of synthetic steps is significantly reduced, resulting fragments retain drug activity or even exhibit improved bioactivity and selectivity [ 14 , 23 ]. The biological significance of this synthetic method is that it allows for the removal of multi-functional groups that are redundant and not essential for binding interactions with target proteins but rather enhance off-target interactions with biological non-targets which engender toxic responses [ 14 , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations